Enhancing the quality and safety of care through training generalist doctors: a longitudinal, mixed-methods study of a UK broad-based training programme - Bullock, Alison (BMJ Open, 2018)
OBJECTIVE: Changing patient demographics make it ever more challenging to maintain the quality and safety of care. One approach to addressing this is the development of training for generalist doctors who can take a more holistic approach to care. The purpose of the work we report here is to consider whether a broad-based training programme prepares doctors for a changing health service. SETTING AND PARTICIPANTS: We adopted a longitudinal, mixed-methods approach, collecting questionnaire data from trainees on the broad-based training (BBT) programme in England (baseline n=62) and comparator trainees in the same regions (baseline n=90). We held 15 focus groups with BBT trainees and one-to-one telephone interviews with trainees post-BBT (n=21) and their Educational Supervisors (n=9). RESULTS: From questionnaire data, compared with comparator groups, BBT trainees were significantly more confident that their training would result in: wider perspectives, understanding specialty complementarity, ability to apply learning across specialties, manage complex patients and provide patient-focused care. Data from interviews and focus groups provided evidence of positive consequences for patient care from BBT trainees’ ability to apply knowledge from other specialties. Specifically, insights from BBT enabled trainees to tailor referrals and consider patients’ psychological as well as physical needs, thus adopting a more holistic approach to care. Unintended consequences were revealed in focus groups where BBT trainees expressed feelings of isolation. However, when we explored this sentiment on questionnaire surveys, we found that at least as many in the comparator groups sometimes felt isolated. CONCLUSIONS: Practitioners with an understanding of care across specialty boundaries can enhance patient care and reduce risks from poor inter-specialty communication. Internationally, there is growing recognition of the place of generalism in medical practice and the need to take a more person-centred approach. Broad-based approaches to training support the development of generalist doctors, which is well-suited to a changing health service.